Enhancing integrated science process skills: Is it better to use open inquiry or guided inquiry model? - Rizky Restu Romadhona; Slamet Suyanto (Biosfer: Jurnal Pendidikan Biologi, 2020)
This study aimed to examine the effectiveness of implementing a real object-based open inquiry model towards integrated science process skills of 10th- grade students in the material of plants (Plantae). This study used quasi-experimental research with nonequivalent control group pretest-posttest design. This study's population was all 10th- of Senior High School S of Yogyakarta, Indonesia, in the academic year grade students of 2018/2019. The technique sampling used in this study was random cluster sampling. The samples consisted of 30 students in the experimental class using the open inquiry model and 30 students in the control class using the guided inquiry model. The instrument used in this study was an essay test consisting of four questions that represent the aspects of science process skills. Analyze data use the independent-sample t-test. The results indicated a significant difference between the means of science process skills post-test of the 10th-grade students in the material of plants. The percentage of N-gain score in the experimental class categorized to low was 0%, categorized to moderate was 17%, and categorized to high was 83%. The most influential aspect of integrated science process skills in the experimental class is communication with 95,33. To sum up, the open inquiry learning model is useful in the 10th-grade students' integrated science process skills, particularly the aspect of communication in plants' material.